F(x) = x² + 4x + 10
f(x) - 10 = x² + 4x
perfect square:
x² + 4x + 4 ⇒ (x + 2)²
(x + 2)² = x(x+2) + 2(x+2) = x² + 2x + 2x + 4 = x² + 4x + 4
f(x) - 10 + 4 = x² + 4x + 4
f(x) - 6 = (x+2)²
f(x) = (x+2)² + 6
Jeremy should use coupon 2 because when you multiply both the sweaters (36) by .25 you get 9, and then you subtract 36 by 9 which is 27.
But when you use coupon 1 you multiply 18 by .40 which is 7.20 where you subtract 18 by 7.20 which is 10.80. You then add 10.80 with 18 which is 28.80.
I don't even know what the question is but I found the same problem and this was the answer
Answer: Option D
Step-by-step explanation:
By definition if we have a function F (x) and perform a transformation of the form
![G (x) = F (x + c)](https://tex.z-dn.net/?f=G%20%28x%29%20%3D%20F%20%28x%20%2B%20c%29)
Then it is true that:
If c is negative the graph of G(x) will be equal to the graph of F(x) displaced horizontally c units to the right
If c is positive, the graph of G(x) will be equal to the graph of F(x) displaced horizontally c units to the left.
Note that in this case the transformation is:
![G (x) = F (x + 9)](https://tex.z-dn.net/?f=G%20%28x%29%20%3D%20F%20%28x%20%2B%209%29)
Then
and ![c> 0](https://tex.z-dn.net/?f=c%3E%200)
Therefore the graph of G(x) will be equal to the graph of F(x) displaced horizontally <em>9 units to the left</em>
The answer is the option D.